Pengaruh Metode Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Biologi Kelas VII di MTs Patra Mandiri Plaju Palembang - ismail Sukardi; Indah Wigati; Imas Masripah (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2015)
The learning process, the teacher always use conventional method so the teacher is more activities and the situation of the activities make the students bored. From the explanation above the result of learning process is less. The writers are interested about the influence of dicovery learning method to improve the students achievement. The research of study was conducted in MTs Patra Mandiri Plaju Palembang academic year 2013/2014. Whether there is influence learning discovery learning methods to the learning outcomes of students in the subjects of Biology class VII MTs Patra Mandiri Plaju Palembang . The purpose of this study is to determine the effect of discovery learning method learning on learning outcomes of students in the subjects of Biology class VII MTs Patra Mandiri Plaju Palembang. Type in this study experiment study using a quantitative approach analysis techniques using t test analysis. The results of the analysis of the posttest valuesobtained is 3.54 at a price t table at 5% significance level and d f = ( 34 +35 ) -2 table = 2.00. Turns t count > t table or 3.54 > 2.00 . This suggest that Ho rejected Ha accepted the hypothesis stated that